SOCIO-CULTURAL PECULIARITIES OF THE SCIENCE LANGUAGE UNDER THE CONDITION OF INFORMATION - Антіпова, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Socio-cultural peculiarities of the science language under the condition of information are considered in the paper. The role of the language as a cultural phenomenon in the process of scientific communication is analyzed.